Analytical studies and experimental examines for flooding-based search algorithms - Barjini, Hassan; Othman, Mohamed; Ibrahim, Hamidah; Udzir, Nur Izura (Springer, 2012)
Flooding search has no knowledge about network topology and ﬁles distribution, thus it oﬀers an attractive method for ﬁle discovery in dynamic and evolving networks. Although ﬂooding can achieve high coverage but it produces exponentially redundant messages in each hop. To improve this searching scheme and reduce redundant messages, there are many ﬂooding-based search algorithms in literature. This pa- per provided analytical study for ﬂooding and ﬂooding-based algorithms. The analytical results provided the best hop threshold point for the optimum growth rate coverage and redundant messages from ﬂooding and ﬂooding-based algorithms. The simulation experiments validated analytical results.